MORTALITAS OPERASI JANTUNG CORONARY ARTERY BYPASS GRAFT DI RSUP DR KARIADI SEMARANG PERIODE JANUARI 2014 - DESEMBER 2014 - Gina Amalia Harahap; Widya Istanto Nurcahyo; Akhmad Ismail (Jurnal Kedokteran Diponegoro (Diponegoro Medical Journal), 2016)
Background: Coronary Heart Disease can occur due to the formation of blockages in the heart arteries. The escalation of patients with this disease can not be separated from the influence of modern and instant lifestyle. One of the management are by doing CABG surgery. To change the society’s paradigm that heart surgery is a scary thing, cardiac surgery at a hospital, the patient's mortality data, can be used as the parametes to measure the quality of heart valve surgery in a hospital.Aim: To find out data on mortality in cardiac surgery department in a case of CABG surgery in Dr. Kariadi Hospital Semarang from January 2014- December  2014.Methods: This study is a descriptive study, with random sampling, using secondary data from medical records of the Medical Record Department,  ICU (Intensive Care Unit) and Installation of Central Surgery Dr. Kariadi Hospital Semarang from January 2014- December  2014. Data are classified by the type of CABG operation by looking at mortality risk factors: gender, age, disease diagnosis, CPB time, cross-clamp time, longer ICU stay, length of ICU ventilators and cause of death.Result: The number of patients of CABG surgery in Dr. Kariadi Hospital Semarang on January 2014- December  2014 were as many as 28 people. The number of patients who died was 4 people (14,3%). Most cause of death was shock cardiogenic5 (50%)Conclusion: During the period of January 2014- December  2014, the death rate of the CABG surgery at Dr. Kariadi Hospital Semarang was 14,3%